(untitled) - American Association for the Avancement of Science (AAAS) (Washington, 2004)
This book analysis of major funding trends for FY 2005 including outyear projections for research and development, and analysis of funding for research about in industry and funding for science, engineering, and mathematics education.
Keywords: Bộ sưu tập nghiên cứu và phát triển,Research and development collection